Associations between T1 white matter lesion volume and regional white matter microstructure in aging. Issue 3 (30th January 2013) - Leritz, Elizabeth C.; Shepel, Juli; Williams, Victoria J.; Lipsitz, Lewis A.; McGlinchey, Regina E.; Milberg, William P.; Salat, David H.
Abstract : White matter lesions, typically manifesting as regions of signal intensity abnormality (WMSA) on MRI, increase in frequency with age. However, the role of this damage in cognitive decline and disease is still not clear, as lesion volume has only loosely been associated with clinical status. Diffusion tensor imaging (DTI) has been used to examine the quantitative microstructural integrity of white matter, and has applications in the examination of subtle changes to tissue that appear visually normal on conventional imaging. The primary goal of this study was to determine whether major macrostructural white matter damage, (total WMSA volume), is associated with microstructural integrity of normal appearing white matter, and if these macrostructural changes fully account for microstructural changes. Imaging was performed in 126 nondemented individuals, ages 43–85 years, with no history of cerebrovascular disease. Controlling for age, greater WMSA volume was associated with decreased fractional anisotropy (FA) in widespread brain regions. Patterns were similar for FA and radial diffusivity but in contrast, WMSA was associated with axial diffusivity in fewer areas. Age was associated with FA in several regions, and many of these effects remained even when controlling for WMSA volume, suggesting the etiology of WMSAs does not fully account for all age‐associated white matter deterioration. These results provide evidence that WMSA volume is associated with the integrity of normal‐appearing white matter. In addition, our results suggest that overt lesions may not account for the association of increasing age with decreased white matter tissue integrity. Hum Brain Mapp 35:1085–1100, 2014. © 2013 Wiley Periodicals, Inc.